2003
DOI: 10.1007/s00216-003-2045-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of p -tyrosol and salidroside in three samples of Rhodiola crenulata and one of Rhodiola kirilowii by capillary zone electrophoresis

Abstract: A capillary zone electrophoresis (CZE) method has been developed for simultaneous assay of two bioactive components (p-tyrosol and salidroside) in Rhodiola crenulata and Rhodiola kirilowii for the first time. Those analytes were successfully separated within 15 min using 50 mmol L(-1) (pH 9.62) borate containing 30% methanol as running buffer. Regression equations revealed linear relationships (correlation coefficients 0.9998-0.9999) between peak area and concentration of the two analytes. The relative standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 5 publications
3
38
0
Order By: Relevance
“…It has been found that pH had significant effect on the effective mobility of p-tyrosol and salidroside. The good separation was achieved only at pH 8.93-10.13 [48]. Therefore, optimization of pH is necessary for CZE analysis of phytochemical bioactive compounds to get good resolution with short analysis time.…”
Section: Buffer Phmentioning
confidence: 95%
See 3 more Smart Citations
“…It has been found that pH had significant effect on the effective mobility of p-tyrosol and salidroside. The good separation was achieved only at pH 8.93-10.13 [48]. Therefore, optimization of pH is necessary for CZE analysis of phytochemical bioactive compounds to get good resolution with short analysis time.…”
Section: Buffer Phmentioning
confidence: 95%
“…Generally, at equal molarities, oligoprotic buffers like citrate will give substantially higher currents than monoprotic species such as acetate. Therefore, type and concentration of the buffer for CZE should be optimized to obtain a good resolution of the interested compounds in a satisfactory time [40,42,43,48,58,63,[87][88][89][90][91][92][93][94][95][96][97][98].…”
Section: Buffer Type and Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the medicinal properties of Rhodiola genus are comparable to those of of Ginseng and Acanthopanax. The advantage of golden root (Rhodiola rosea) is the fact that no side effects are observed [2,3]. Among the all species of Rhodiola 20 has been used in the traditional medicine of Asia: R. rosea, R. alterna, R. brevipetiolata, R. crenulata, R. kirilowii, R. quadrifida, R. sachalinensis and R. sacra [4].…”
Section: Introductionmentioning
confidence: 99%